2002
DOI: 10.1046/j.1365-2389.2002.00473.x
|View full text |Cite
|
Sign up to set email alerts
|

Variation of hydraulic conductivity in a tilled soil

Abstract: Summary Tillage increases the spatial variation of the structure and saturated hydraulic conductivity of the soil. Recent advances have related morphological macroscopic features of the structure to the cultivation operations responsible for compaction, fragmentation and displacement of the soil. This description is based on a compartmentation of the tilled soil, vertically (seed bed, ploughed layer, and untilled soil) and horizontally (below wheel tracks, between wheel tracks). Between the wheel tracks we dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
48
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(58 citation statements)
references
References 23 publications
(28 reference statements)
6
48
1
Order By: Relevance
“…range. The same effect of tillage on k m values have already been observed by Coutadeur et al (2002). Further, the increase of k m took place within a very similar water potential range (À0.5 to À0.2 kPa).…”
Section: K(h) Measurementssupporting
confidence: 81%
See 1 more Smart Citation
“…range. The same effect of tillage on k m values have already been observed by Coutadeur et al (2002). Further, the increase of k m took place within a very similar water potential range (À0.5 to À0.2 kPa).…”
Section: K(h) Measurementssupporting
confidence: 81%
“…The former will alter both water retention and hydraulic conductivity while the latter will essentially modify the hydraulic conductivity. The lower conductivity at low potential may be due to the disruption of pore continuity as a result of tillage (Logsdon et al, 1990;Reynolds et al, 1995;Coutadeur et al, 2002). On the other hand, the higher conductivity at high potential may be due to the porosity created by tillage and resulting in large inter-clod or inter-aggregate voids that are interconnected to the difference of the smaller-sized pores (e.d.b3 mm).…”
Section: K(h) Measurementsmentioning
confidence: 99%
“…It was found that the hydraulic conductivity of soil decreased by 40% in the wheelings compared to the areas between the tracks (Coutadeur et al, 2002). The timing of ploughing has an important effect on runoff generation.…”
Section: Arable Agriculturementioning
confidence: 99%
“…This method is used to describe the soil structure of the tilled layer of agricultural fields. It is based on the visual observation of soil macroscopic features on the vertical face of a large soil pit oriented perpendicular to the tillage direction (Coutadeur et al, 2002;Roger-Estrade et al, 2000). The soil profile was divided into vertical and horizontal compartments according to the effects of the tillage implements and the internal structure of each of these compartments.…”
Section: Site and Compost Characteristicsmentioning
confidence: 99%